Assessing the Impact of Digital Tools on Taungya Maize Farmers in Okomu Forest Reserve Nigeria - Adebayo Samson Adeoye; Adebayo David Samuel; Oluwole Olalekan Oke (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Rural farmers face challenges accessing agricultural information and inputs, affecting their livelihoods. This study addresses the gap in digital device availability among farmers around Okomu forest reserve, Edo State. There was a three-staged multistage sampling technique used for the selection of 20 respondents from four (4) surrounding settlements, namely Sikoloba, Iguefolo, Okomu, and Agbonmoba, resulting in a total of 80 (eighty) respondents in May to October 2024 around Okomu reserve. The objectives examined were demographic characteristics of farmers, types of ICT devices used, extent of radio and mobile phone usage, and the influence of these technologies. The study adopted a well-structured questionnaire for data collection and analysis using frequencies, chi-square, and PPMC. Consequently, demographics revealed that about 64.0% of the respondents were men. ICT devices such as radio, television, and mobile phones significantly improved farmers' income and knowledge, exposing them to modern maize farming techniques through agricultural programs, documentaries, and farmer-to-farmer communication. Chi-square statistic showcased a significant association between demographics of age (χ²= 34.24), marital status (χ²= 25.78), education (χ²= 56.89), and secondary occupation (χ²= 20.31), and ICT utilization. Also, a significant correlation existed at an R-value equal to 0.82 between the extent of ICTs utility and its influence on taungya maize farmers' production.